European component of the AIDA mission to a binary asteroid: Characterization and interpretation of the impact of the DART mission. Issue 8 (15th October 2018) - Michel, Patrick; Kueppers, Michael; Sierks, Holger; Carnelli, Ian; Cheng, Andy F.; Mellab, Karim; Granvik, Mikael; Kestilä, Antti; Kohout, Tomas; Muinonen, Karri; Näsilä, Antti; Penttila, Antti; et al.
Abstract: The European component of the joint ESA-NASA Asteroid Impact & Deflection Assessment (AIDA) mission has been redesigned from the original version called Asteroid Impact Mission (AIM), and is now called Hera. The main objectives of AIDA are twofold: (1) to perform an asteroid deflection test by means of a kinetic impactor under detailed study at NASA (called DART, for Double Asteroid Redirection Test); and (2) to investigate with Hera the changes in geophysical and dynamical properties of the target binary asteroid after the DART impact. This joint mission will allow extrapolating the results of the kinetic impact to other asteroids and therefore fully validate such asteroid deflection techniques. Hera leverages technology and payload pre-developments of the previous AIM, and focuses on key measurements to validate impact models such as the detailed characterisation of the impact crater. As such, AIDA will be the first documented deflection experiment and binary asteroid investigation. In particular, it will be the first mission to investigate a binary asteroid, and return new scientific knowledge with important implications for our understanding of asteroid formation and solar system history. Hera will investigate the smallest asteroid visited so far therefore providing a unique opportunity to shed light on the role cohesion and Van der Waals forces may play in the formation and resulting internal structure of such small bodies.